Boron Neutron Capture Therapy (BNCT) using Compact Neutron generator - Anggraeni Dwi Susilowati; Kusminarto Kusminarto; Yohannes Sardjono (Indonesian Journal of Physics and Nuclear Applications, 2016)
Boron Neutron Capture Therapy (BNCT) must be appropriate with ﬁve criteria from IAEA. These criteria in order to prevent neutron beam output harm the patient. It can be by using Collimator of neutron source Compact Neutron Generator (CNG) and Monte Carlo simulation method with N particles 5 .CNG is developed by deuteriumtritium reaction (DT) and deuterium-deuterium (DD) reaction. The manufacture result of the collimator is obtained epithermal neutron ﬂux value of 1.69e-9 n/cm^2s  for D-T reaction and 8e6 n/cm^2s for D-D reaction, ratio of epithermal and thermal is 1.95e-13 Gy cm^2/n for D-T reaction and for D-D reaction, ratio of fast neutron component is 1.69e-13 Gy cm^2/n for D-T reaction and for D-D reaction, ratio of gamma component is 1.18e-13 Gy cm^2/nfor D-T reaction and for D-D reaction. The Latest reaction is current ratio 0.649 for D-T reaction and 0.46 for D-D reaction.